A study on “repeated reading of the text” enhances writing skill among year five pupils of Saint Francis Xavier Primary School Kuching Sarwawak / Helen Kumew Rona - Rona, Helen Kumew (2004)
This academic writing is conducted with the purpose to investigate the effectiveness of repeated reading on writing guided essays among Year Five pupils of Saint Francis Xavier Primary School. Kuching, Sarawak. The data from the study aims to examine whether or not repeated reading enhances writing skills. The feedbacks from the pupils through the questionnaire help in the study. A total offorty pupils consisting oftwenty girls and sixteen boys participated in the study as respondents. The data ofthe pre-test and post-test are shown in tables and graphs. The data from the pupils’ feedback are shown in tables and further detailed explanation is given after each table. This study supports the hypothesis that repeated reading enhances writing skills among pupils. Besides having better test results, the pupils find that writing guided essay after repeated reading easier and that they are more confident in doing their test. Nevertheless, the finding ofthis study has its limitation. It does not represent the findings on other schools.